DEMINERALIZATION OF MARINE AND FRESHWATER SEDIMENTS FOR CP/MAS 13C NMR ANALYSIS - Gelinas Y.; Baldock J.A.; Hedges J.I. (My University, 2001)
A method was developed to demineralize sediment trap material and marine sediments containing labile organic matter (OM), in preparation for cross polarization and magic angle spinning (CP/MAS) solid-state 13C NMR analysis. Carbonate and silicate minerals were dissolved with HCl and a mixture of dilute HCl/HF, respectively. Demineralization kinetics were assessed for a range of freshwater and marine sediments, as well as pure mineral and organic samples. For samples with a very low organic carbon (OC) concentration (<1 wt.%) and samples containing a large fraction of acid-soluble oc, the organic molecules solubilized during dissolution mineral were recovered by freeze-drying supernatants following (i) removal dissolved calcium residual hf caf2 precipitation, (ii) removal of the dissolved paramagnetic metals by sulfide precipitation, and (iii) desalting using ion retardation chromatography. When applied to a wide range of freshwater and marine particles, demineralization resulted in OC enrichment factors that varied between 2.2 and 20.8, with losses representing less than 20.5% of the initial OC content. X-ray diffraction and fluorescence analysis of the natural and demineralized samples showed that minerals and paramagnetic metals were effectively removed. While molecular fractionation might be substantial when the mineral constituents were dissolved with HCl and HF, the small changes (<11%) in the (C/N)a and (H/C)a ratios when the acid-soluble organic matter was recovered suggest that the molecular composition of the organic fraction was not appreciably altered. In combination with CP/MAS 13C NMR spectroscopy, this demineralization method allows comprehensive elucidation of the chemical structure of total OC, especially in samples with very low OC concentrations and/or with a significant fraction of chemically labile organic compounds.
Keywords: DEMINERALIZATION; SEDIMENTARY ORGANIC MATTER; SEDIMENT; CP/MAS 13C NMR